Equation for Rapid Calculation of the Standard Deviation - ดวงศร พงษ์วุฒิ (KKU Science Journal, 2013)
This paper proposes rapid standard deviation equation for determining the standard deviation of variable-size data. The novel method calculates the standard deviation in an accumulative way: it requires only new observation to be included, instead of using whole data, in calculation. The method has the running time of O(N) instead of the traditional O(N2). The proposed rapid standard deviation equation depends on the following factors: new observation(xN), the amount of current data size (N), the average of the value of current data ( ), and standard deviation of previous data set ( ’). The equation is in a compact form, easy to understand and apply to data sets.